Oinophoroi of Seleukeia Sidera - Sönmez, Burak (Rei Cretariae Romanae Fautorum Acta, 2023)
A large number of vessels in the form of oinophoroi were found during the studies carried out in 1993 and since 2017 in Seleukeia Sidera in the Pisidia Region (Turkey). This group can be dated between the 4th to the 7th centuries AD. In the region, this form was found most intensely in Sagalassos, which is also known for its production. A fewer number of examples were also identified in the surrounding cities. When compared with these cities, the oinophoroi of Seleukeia Sidera become prominent in terms of number and variety. The group in this study is discussed together with archaeometric analyses. Analyses show that the oinophoroi of Seleukeia Sidera have the same elemental composition as the Late Roman red slipped wares, which were produced in or around Seleukeia Sidera.